2015
DOI: 10.1080/10408398.2015.1046547
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal physical technologies to decontaminate and extend the shelf-life of fruits and vegetables: Trends aiming at quality and safety

Abstract: Minimally processed fruits and vegetables are one of the major growing sectors in food industry. This growing demand for healthy and convenient foods with fresh-like properties is accompanied by concerns surrounding efficacy of the available sanitizing methods to appropriately deal with food-borne diseases. In fact, chemical sanitizers do not provide an efficient microbial reduction, besides being perceived negatively by the consumers, dangerous for human health, and harmful to the environment, and the convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 125 publications
(151 reference statements)
0
54
0
3
Order By: Relevance
“…Several authors (Schluter et al ., ; Thirumdas et al ., ; Pinela & Ferreira, ) consider postharvest CP treatment as a green/environment‐friendly technology as it requires low energy and water consumption. According to Herrmann et al .…”
Section: Cold Plasma Prospects and Constraintsmentioning
confidence: 99%
“…Several authors (Schluter et al ., ; Thirumdas et al ., ; Pinela & Ferreira, ) consider postharvest CP treatment as a green/environment‐friendly technology as it requires low energy and water consumption. According to Herrmann et al .…”
Section: Cold Plasma Prospects and Constraintsmentioning
confidence: 99%
“…This aspect has been less attended in the previous research works and requires further investigations. The changes made by plasma to the formulation of food recipes or conformation of food components could have unforeseen consequences on the final product quality (Pinela and Ferreira, 2015) and safety, as this would result in the temporary or permanent removal of some protective effects such as the lowering of water activity and reduction in antioxidant capacity. Accordingly, there is still a need for more comprehensive studies on the consequences of plasma protein manipulation in both in vitro and in vivo conditions to ensure the health of food supplies.…”
Section: Challenges and Future Research Prospectmentioning
confidence: 99%
“…With respect to microorganisms and virus types, many studies showed that the HPP treatment does not work the same way for all taxa [37,38]. Indeed, different species can have varying pressure resistance and the stage of growth of bacteria is also important in determining pressure resistance: for example, cells in stationary or dormant phase are more pressure resistant than those in the exponential phase.…”
Section: Effects On Microorganisms and Virusesmentioning
confidence: 99%
“…HPP can cause damage to the virus envelope, preventing the virus particles binding to cells or even complete dissociation of virus particles, which may be either fully reversible or irreversible, depending on the pressure. Prions, associated with neurological disorders in animals and humans, are generally even more difficult to destroy than bacterial spores [38].…”
Section: Effects On Microorganisms and Virusesmentioning
confidence: 99%